Entre a história e a utopia: o educador de rua no Projeto Axé - Souza, Aline Moura de Melo (2007)
The objective of this work is to reflect how the street educators that work in the Axe Project have articulated their utopic thinking, typical of the start of the project, with the historic thinking that prevailed after 15 years of practice and after significant change in the third sector. The theoretical framework used is based in the identity sintagma as metamorphosis in search of emancipation, developed by professor Antonio da Costa Ciampa inside the research group about Social Identity as a Human Metamorphosis, linked to the Post Graduate Studies Program in Social Psychology of PUC-SP. Also, we used notions of utopic thinking, which makes us fight for social causes, and historical thinking, which examines from a critical standpoint how the facts are occurring in the timeline of history (Habermas, 1987). The empirical research is based on interview classified by Minayo (1999) as non directive centered or focalized interview . In this type of interview the conversation is conducted without a previous developed script. Three emblematic subjects were analyzed. One is satisfied in the Axe Project, the other wants out and the third had already left. The results found were not dependent of the status of the subject in Axe Project. The observation revealed that it is possible to articulate history and utopia. Or, to put in other words, that even facing a tough history, not to lose the sense of utopia. The study indicates that whoever embraces the utopia thinking, and wants it to become reality, has to keep up with history pace and to develop the flexibility to reinvent his own utopic projects, therefore changing his emancipatory project without losing the utopic perspective that was his original motivation. Changing, emancipating, to become a post-conventional subject. The conclusion of this work is that it s not only possible to articulate both movements but also likely that those professionals who are able to do it tend to have a post-conventional stance in life